2001
DOI: 10.1152/jappl.2001.91.3.1467
|View full text |Cite
|
Sign up to set email alerts
|

Selected Contribution: Synergism between TNF-α and IL-1β in airway smooth muscle cells: implications for β-adrenergic responsiveness

Abstract: In human cultured airway smooth muscle cells, interleukin (IL)-1 beta increases cyclooxygenase (COX)-2 expression and PGE(2) release, ultimately resulting in decreased beta-adrenergic responsiveness. In this study, we aimed to determine whether tumor necrosis factor-alpha (TNF-alpha) synergizes with IL-1 beta in the induction of these events. TNF-alpha alone, at concentrations up to 10 ng/ml, had no effect on COX-2 protein expression; at concentrations as low as 0.1 ng/ml, it significantly enhanced the ability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
39
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 33 publications
9
39
1
Order By: Relevance
“…This work concurs with other reports examining p38 MAPK-mediated regulation of COX-2 expression in airway smooth muscle cells stimulated with IL-1␤ and TNF-␣ (16,22,42). The experiments presented here more clearly delineate that p38 MAPK, and not ERK MAPK, contributes to cytokine-stimulated COX-2 expression in response to a more complex inflammatory stimulus.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This work concurs with other reports examining p38 MAPK-mediated regulation of COX-2 expression in airway smooth muscle cells stimulated with IL-1␤ and TNF-␣ (16,22,42). The experiments presented here more clearly delineate that p38 MAPK, and not ERK MAPK, contributes to cytokine-stimulated COX-2 expression in response to a more complex inflammatory stimulus.…”
Section: Discussionsupporting
confidence: 92%
“…The data presented here further describe expression of COX-2 in cultured BSMC exposed to a complex proinflammatory stimulus of IL-1␤, TNF-␣, and IFN-␥, which has been previously shown to induce COX-2 expression in cells isolated from human tracheal smooth muscle (3). Although several reports in the literature have examined COX-2 expression in response to IL-1␤ or a combination of IL-1␤ and TNF-␣ in airway smooth muscle (22,26,42), our data suggest that the addition of IFN-␥ to the cytokine stimulus synergistically stimulates PGE 2 synthesis from endogenous arachidonic acid and also contributes to increases in COX-2 expression. Therefore, the use of a stimulus that includes IFN-␥ may yield important information about the regulation of inflammatory mediators.…”
Section: Discussioncontrasting
confidence: 63%
“…The expression of PGE synthases has not been previously reported in HASM cells, although COX-2 expression and PGE 2 production have been shown to be increased by IL-1␤, which is in accord with our results. 60 Similar to the present results, the expression of PGE synthases and the up-regulation of mPGES-1, COX-2, and PGE 2 in response to IL-1␤ and TNF-␣ have also been demonstrated in primary human vascular smooth muscle cells. 61,62 In one of those studies, 62 the authors also demonstrated the lack of mPGES-1 induction in HUVEC cells, which is in accord with our results obtained from HUVEC cells.…”
Section: Discussionsupporting
confidence: 91%
“…We previously reported that TNF-␣ has only minimal effects on the ability of ISO to relax HASM cells (18). To confirm that TNF-␣ also does not alter ISO-induced changes in cAMP formation, as has previously been reported (22) (Fig.…”
Section: Effect Of Tnf-␣ On Iso-induced Creb Phosphorylation and Cre-supporting
confidence: 76%
“…In contrast to IL-1␤, TNF-␣ did not alter basal CRE-driven gene expression in HASM cells (Fig. 8), likely because TNF-␣ does not induce COX-2 expression in HASM cells (18). However, similar to IL-1␤, TNF-␣ did attenuate the ability of ISO to induce luciferase expression (Fig.…”
Section: Effect Of Tnf-␣ On Iso-induced Creb Phosphorylation and Cre-mentioning
confidence: 86%